Methods of sampling benthic invertebrates in lotic habitats: A spatial and temporal evaluation - da Cunha, Larissa Lima [UNESP]; Alves, Maria Ines Bulgari [UNESP]; Ono, Erika Ramos [UNESP]; Uieda, Virginia Sanches [UNESP] (FapUNIFESP (SciELO), 2019)
Aim: We compared the effectiveness of two sampling devices, the Surber sampler and the D-frame net, commonly used in the analysis of invertebrate fauna structure in biomonitoring programs. These programs use the response of benthic invertebrates to assess changes in aquatic ecosystems because they respond quickly to spatial and temporal variations. However, the lack of consensus on the best method of sampling the fauna may reduce the quality of these studies. Methods:We evaluated both devices in four structurally different reaches of streams, two in places with preserved riparian vegetation and two occurring in places with many anthropic disturbances. We repeated the analysis at the dry season of two consecutive years. Results: The two samplers were equally effective in analyzing the benthic fauna and sensitive enough to identify spatial and temporal variation in the structure of this fauna, influenced by the presence or absence of riparian vegetation, by the position of the reach with this vegetation (upstream or downstream of the reach without vegetation) and the characteristics of the substrate. Conclusions: The analyzed fauna structure was similar for the two samplers, but we consider the use of Surber more advantageous and effective because it collects a smaller number of individuals, reducing the time of processing and identifying in the laboratory, and allows a better definition of the area sampled.
Métodos de amostragem de invertebrados bentônicos em ambientes lóticos: Uma avaliaçao espacial e temporal
Keywords: D-frame net; Quantitative sampling; Surber sampler; Tropical stream